2016
DOI: 10.1111/nep.12636
|View full text |Cite
|
Sign up to set email alerts
|

Estimating glomerular filtration rate by serum creatinine or/and cystatin C equations: An analysis of multi‐centre Chinese subjects

Abstract: The Fengscr-cys equation appeared to achieve the best performance for GFR estimation in overall Chinese adult patients. However, further research is warranted to improve the accuracy of available equations in GFR less than 60 mL/min per 1.73 m(2) individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 27 publications
0
12
0
1
Order By: Relevance
“…Five studies showed uncertain risk of bias in the flow and timing. Some studies [ 16 , 18 , 22 , 23 , 25 ] enrolled mostly female or male patients, who might not be representative of the target population, and so potential spectrum bias existed.…”
Section: Resultsmentioning
confidence: 99%
“…Five studies showed uncertain risk of bias in the flow and timing. Some studies [ 16 , 18 , 22 , 23 , 25 ] enrolled mostly female or male patients, who might not be representative of the target population, and so potential spectrum bias existed.…”
Section: Resultsmentioning
confidence: 99%
“…One is serum cystatin C-base eGFR equation and the other is cystatin C combined with creatinine-based equation. The precision of the two equations has been validated [ 35 , 36 ]. In the present study, the eGFRs derived from the three equations were all closely related to carotid WSS.…”
Section: Discussionmentioning
confidence: 99%
“…Using fasting serum to derive serum creatinine concentration (Scr, mg/dL), we calculated estimated glomerular filtration rates (eGFR), using the following set of equations [32] which were modified based on the Chronic Kidney Disease-Epidemiology (CKD-EPI) equations and acquired the best performance among serum creatinine-based equations validated among Chinese population in Ye et al [33]. Reduced renal function was defined as eGFR of <60 mL/min/1.73 m 2 [34].…”
Section: Methodsmentioning
confidence: 99%